Phenoxazine modification-based cuprous iodide cluster material as well as preparation method and application thereof

The preparation of copper iodide-based cluster materials through phenoxazine modifications solved the problem of 3CC excited state radiation limitation in Cu4I4 type copper cluster materials, achieving higher efficiency of electroluminescent device preparation and material performance improvement.

CN119462759AActive Publication Date: 2025-02-18HEILONGJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411597828.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

In the existing Cu4I4 type copper cluster materials, the radiation limitation of the 3CC excited state hinders the further improvement of its optical properties.

Method used

The copper iodide-based cluster materials were prepared by phenoxazine modification, regulating the composition of the excited state, and improving electrical properties and solution processing properties.

Benefits of technology

A higher efficiency electroluminescent device preparation is achieved, improving the electron injection and transmission capability of the material, reducing the driving voltage, and enhancing the luminous efficiency and brightness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462759A_ABST
    Figure CN119462759A_ABST
Patent Text Reader

Abstract

The invention provides a phenoxazine modification-based cuprous iodide cluster material as well as a preparation method and application thereof, and belongs to the technical field of luminescent materials. According to the four cuprous iodide cluster materials based on phenoxazine modification provided by the invention, the cuprous iodide cluster modified by phenoxazine and the cubic alkane cluster modified by an asymmetric single donor for improving molecular rigidity are used for regulating and controlling the composition of an excited state and enhancing a ligand-related charge transfer effect. The asymmetric structure prevents mutual accumulation among molecules and inhibits quenching. The dibenzofuran functional group is high in molecular rigidity and has a plurality of modification sites, diphenylphosphine is introduced into 4 and 6 sites, and the distance between P and P can just accommodate Cu4I4. Phenoxazine or phenyl phenoxazine is used as a strong donor group to regulate and control the composition of an excited state and improve the electrical properties. A diphenylphosphine functional group is used as an anchor point to fix a cluster core and provide a coordination site, and P can be coordinated with Cu. CuX has abundant reserves and is environment-friendly, so that the cluster structure is more diversified, and abundant excited state composition is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a phenoxazine-modified cuprous iodide cluster material, a preparation method of the material, use of the material as a luminescent material, preparation of an electroluminescent device using the material, and a preparation method of the electroluminescent device. Background Art

[0002] Organic semiconductor electroluminescent devices, especially organic light-emitting diodes (OLEDs), are widely used in display and lighting fields such as smart phones and televisions due to their outstanding advantages such as light weight, low energy consumption, flexibility, self-luminescence, and wide imaging viewing angle. In the past decade, thermally activated delayed fluorescence (TADF) materials have been used as a new type of organic optoelectronic materials. Metal clusters with precise atomic structures have attracted much attention due to their structural diversity, excellent photophysical properties and potential application prospects. For example, metal clusters have great application potential in chiral luminescence, catalysis, detection, and device applications. This has enriched the research on metal cluster materials and laid a solid foundation for the diversity of materials. Compared with other precious metal clusters, copper clusters have abundant reserves and low prices, and copper has weak coupling. Under certain conditions, RISC from T1 to S1 can be achieved, and they have TADF characteristics; copper clusters have greater molecular rigidity due to their multi-core structure.

[0003] Currently, the most widely studied copper clusters are Cu4I4-type copper clusters, which have attracted much attention due to their interesting color-changing luminescence, which can be attributed to two triplet excited states: cluster-centered (3CC) and halide / metal-to-ligand charge-transfer (3(X+M)LCT) emission states. However, in the face of increasing performance requirements, the inherent radiation limitation of the 3CC excited state has hindered the further improvement of its optical performance. Summary of the invention

[0004] In view of this, in order to solve the technical problem that the inherent radiation limitation of the 3CC excited state in the prior art hinders the optical properties of Cu4I4 type copper cluster materials, in the first aspect, the present invention provides a cuprous iodide cluster material based on phenoxazine modification, which can regulate the composition of the excited state, improve the electrical properties, and improve the solution processing performance. The diphenylphosphine functional group serves as an "anchor point" to fix the cluster core and provide a coordination site, and P can coordinate with Cu. CuX has abundant reserves and is environmentally friendly, which can make the cluster structure more diverse and provide a rich excited state composition.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] The phenoxazine-modified cuprous iodide cluster material has a structure of one of the following compounds 1 to 4:

[0007]

[0008]

[0009] Preferably, the method comprises the following steps:

[0010] (1) Under anhydrous and oxygen-free conditions, precursor 1 reacts with tetramethylethylenediamine in an ether solution with n-butyl lithium, diphenylphosphine chloride and hydrogen peroxide to obtain precursor 2;

[0011]

[0012] (2) Precursor 2 reacts with N-bromosuccinimide in acetic acid and sulfuric acid to obtain precursors 3 and 4;

[0013]

[0014] (3) Under anhydrous and oxygen-free conditions, precursors 3 and 4 react with phenoxazine in a xylene solution with palladium acetate, potassium tert-butoxide and tri-tert-butylphosphine to obtain precursors 5 and 6, respectively;

[0015]

[0016] (4) Under anhydrous and oxygen-free conditions, precursor 5 and precursor 6 react with trichlorosilane in a toluene solution to obtain precursor 7 and precursor 8, respectively;

[0017]

[0018] (5) Under anhydrous and oxygen-free conditions, precursor 7 and precursor 8 react with cuprous iodide in a dichloromethane solution to obtain compound 1 and compound 2, respectively;

[0019] (6) Under anhydrous and oxygen-free conditions, precursor 9 reacts with phenoxazine in N,N-dimethylformamide solution with potassium carbonate and copper powder to obtain precursor 10;

[0020]

[0021] (7) Under anhydrous and oxygen-free conditions, the precursor 10 reacts with the borate ester in a 1,4-dioxane solution by adding potassium acetate and ferrocene to obtain the precursor 11;

[0022]

[0023] (8) Under anhydrous and oxygen-free conditions, precursor 11 reacts with precursor 3 and precursor 4 in a toluene solution with tetrakistriphenylphosphine palladium and sodium hydroxide to obtain precursor 12 and precursor 13, respectively;

[0024]

[0025] (9) Under anhydrous and oxygen-free conditions, precursor 12 and precursor 13 are reacted with trichlorosilane in a toluene solution to obtain precursor 14 and precursor 15, respectively;

[0026]

[0027] (10) Under anhydrous and oxygen-free conditions, precursor 14 and precursor 15 were reacted with cuprous iodide in a dichloromethane solution to obtain compound 3 and compound 4, respectively.

[0028] Preferably, the method specifically comprises the following steps:

[0029] (1) Under anhydrous and oxygen-free conditions, the precursor 1 is mixed with an ether solution of tetramethylethylenediamine, the reaction system is cooled, and the temperature is controlled for half an hour; n-butyl lithium is added dropwise with a constant pressure dropper, and the temperature is controlled for half an hour after the addition is completed, and the reaction is carried out at room temperature; the temperature is then controlled for half an hour; diphenylphosphine chloride is added dropwise with a constant pressure dropper, and the reaction is carried out at room temperature; hydrogen peroxide is added dropwise with a constant pressure dropper, and after oxidation, it is extracted with water and dichloromethane, the organic layers are combined, dried, and purified by column chromatography using a mixed solvent of dichloromethane and ethyl acetate as an eluent to obtain a precursor 2;

[0030] (2) Precursor 2 is mixed with glacial acetic acid and H 2 SO 4 , operate under an ice-water bath with less ice, after the dripping is complete, move into an oil bath for reaction, and add NBS in batches; after the reaction is completed, quench with ice cubes, extract with water and dichloromethane, combine the organic layers, dry, and purify by column chromatography using a mixed solvent of dichloromethane and ethyl acetate as the eluent to obtain precursors 3 and 4;

[0031] (3) Under anhydrous and oxygen-free conditions, precursor 3 and precursor 4 are reacted with phenoxazine, palladium acetate and potassium tert-butoxide in a xylene solution, and then tri-tert-butylphosphine is added. After passing water, the mixture is moved into an oil bath for reaction. After the reaction is completed, the mixture is quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried over anhydrous sodium sulfate. The organic layer is spin-dried and purified by wet column chromatography using ethyl acetate and dichloromethane as eluents to obtain precursor 5 and precursor 6, respectively.

[0032] (4) Under anhydrous and oxygen-free conditions, precursor 5 and precursor 6 were reacted with trichlorosilane in a toluene solution, respectively, and then moved into an oil bath for reaction. After the reaction was completed, the reaction was quenched with ice water, extracted with water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried and purified by wet column chromatography using petroleum ether and dichloromethane as eluents to obtain precursor 7 and precursor 8, respectively.

[0033] (5) Under anhydrous and oxygen-free conditions, precursor 7 and precursor 8 were reacted with cuprous iodide in a dichloromethane solution, respectively, and then moved into an oil bath for reaction after passing water. The solids were filtered out with acetonitrile to obtain compound 1 and compound 2, respectively;

[0034] (6) Under anhydrous and oxygen-free conditions, precursor 9 reacts with phenoxazine in N,N-dimethylformamide solution with potassium carbonate and copper powder, and then moves into an oil bath for reaction. After the reaction is completed, it is quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer is spin-dried and purified by wet column chromatography using petroleum ether as the eluent to obtain precursor 10;

[0035] (7) Under anhydrous and oxygen-free conditions, the precursor 10 and the borate ester were reacted in a 1,4-dioxane solution with potassium acetate and ferrocene, and then moved into an oil bath for reaction. After the reaction was completed, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried over anhydrous sodium sulfate. The organic layer was spin-dried and purified by flash column chromatography with petroleum ether and dichloromethane as the eluent to obtain the precursor 11;

[0036] (8) Under anhydrous and oxygen-free conditions, precursor 11 is reacted with precursor 3 and precursor 4 in a toluene solution with tetrakistriphenylphosphine palladium and sodium hydroxide, and water is added with a syringe. After the water is passed, the mixture is moved into an oil bath for reaction. After the reaction is completed, the mixture is quenched with ice water, extracted with water and dichloromethane, and dried with anhydrous sodium sulfate. The organic layer is spin-dried and purified by wet column chromatography using ethyl acetate as the eluent to obtain precursor 12 and precursor 13, respectively.

[0037] (9) Under anhydrous and oxygen-free conditions, precursor 12 and precursor 13 were reacted with trichlorosilane in a toluene solution, respectively, and then moved into an oil bath for reaction. After the reaction was completed, the precursors were quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried over anhydrous sodium sulfate. The organic layer was spin-dried and purified by wet column chromatography using petroleum ether and dichloromethane as eluents to obtain precursors 14 and 15, respectively.

[0038] (10) Under anhydrous and oxygen-free conditions, precursor 14 and precursor 15 were reacted with cuprous iodide in a dichloromethane solution, respectively. After passing water, the mixture was moved into an oil bath for reaction. The solids were filtered out with acetonitrile to obtain compounds 3 and 4, respectively.

[0039] In a second aspect, the present invention provides the above-mentioned phenoxazine-modified cuprous iodide cluster material or the phenoxazine-modified cuprous iodide cluster material prepared by the above-mentioned preparation method for use as a luminescent material.

[0040] Preferably, the luminescent material is a near-ultraviolet to ultraviolet luminescent thermally excited delayed fluorescent material.

[0041] In a third aspect, the present invention provides the use of the above-mentioned phenoxazine-modified cuprous iodide cluster material or the phenoxazine-modified cuprous iodide cluster material prepared by the above-mentioned preparation method in an electroluminescent device.

[0042] In a fourth aspect, the present invention provides an electroluminescent device, wherein the above-mentioned phenoxazine-modified cuprous iodide cluster material or the phenoxazine-modified cuprous iodide cluster material prepared by the above-mentioned preparation method and a doped light-emitting layer of a host material is spin-coated on a hole injection layer.

[0043] Preferably, the main material is bis-4-(N-carbazolylphenyl)phenylphosphine oxide.

[0044] In a fifth aspect, the present invention also provides a method for preparing the above electroluminescent device, comprising the following steps:

[0045] 1. preparing a conductive anode layer;

[0046] 2. preparing a hole injection layer;

[0047] 3. preparing a light-emitting layer;

[0048] 4. preparing an electron transport layer;

[0049] 5. preparing an electron injection layer;

[0050] 6. Prepare a cathode conductive layer, encapsulate, and obtain an electroluminescent device of phenoxazine-modified cuprous iodide clusters.

[0051] Preferably, the method specifically comprises the following steps:

[0052] 1. Preparation of Conductive Anode Layer

[0053] preparing the conductive anode layer on the substrate layer;

[0054] 2. Preparation of hole injection layer

[0055] Spin coating a hole injection layer on the conductive anode layer, which is poly (3,4-ethylenedioxythiophene): polystyrene sulfonate) (PEDOT:PSS), to obtain a hole injection layer;

[0056] 3. Preparation of the Light Emitting Layer

[0057] Spin coating the light-emitting layer on the hole injection layer, wherein the light-emitting layer is bis-4-(N-carbazolyl)phenyl)phenylphosphine oxide as a main material and doped with 20% of a phenoxazine-modified cuprous iodide cluster material to obtain the light-emitting layer;

[0058] 4. preparing an electron transport layer;

[0059] TmPyPB material is evaporated on the light-emitting layer (preferably the evaporation condition is a vacuum degree of 2×10 -4 pa, evaporation rate is 2nms -1 ~3nms -1 ), to obtain the electron transport layer;

[0060] 5. preparing an electron injection layer;

[0061] Vapor depositing LiF material on the electron transport layer to obtain the electron injection layer;

[0062] 6. Preparation of cathode conductive layer,

[0063] Metal Al is evaporated on the electron injection layer (preferably with a vacuum degree of 2×10 -4 pa and evaporation rate is 5nms -1 ~7nms -1 ), to obtain the cathode conductive layer, and then to encapsulate to obtain the electroluminescent device.

[0064] The present invention finds in molecular design that copper clusters can provide rich excited state compositions, and have abundant reserves and diverse structures. The electron-donating groups on the ligands can improve electrical properties, improve solution processability, and regulate excited state compositions. The interaction between the ligands and the cluster cores can regulate electronic transitions. The cluster cores of the cubane configuration improve the rigidity of the molecules, and the diphenylphosphine groups further increase steric hindrance. The losses caused by non-radiative transitions when the molecules are excited are reduced.

[0065] The invention improves the interaction between the donor and the acceptor in the molecule, regulates the luminescence of the material, and realizes the preparation of the electroluminescent device with higher efficiency.

[0066] The present invention provides a cuprous iodide cluster material based on phenoxazine modification, wherein the cuprous iodide cluster modified with phenoxazine improves molecular rigidity, and the asymmetric single donor modified cubane cluster is used to regulate the composition of the excited state and enhance the charge transfer effect related to the ligand. The asymmetric structure can prevent the mutual accumulation of molecules and inhibit quenching. The dibenzofuran functional group has strong molecular rigidity and has multiple modification sites. Diphenylphosphine is introduced at the 4 and 6 positions, and the distance between PP can just accommodate Cu4I4. Phenoxazine or phenylphenoxazine, as a strong donor group, can regulate the excited state composition, improve electrical properties, and improve solution processing performance. The diphenylphosphine functional group serves as an "anchor point" to fix the cluster core and provide a coordination site at the same time, and P can coordinate with Cu. CuX has abundant reserves and is environmentally friendly, which can make the cluster structure more diverse and provide a rich excited state composition.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] (1) The present invention uses phenoxazine or phenylphenoxazine as a donor and dibenzofuran as an acceptor to construct a donor-acceptor structure, and the polarization effect of the phosphine oxygen group significantly enhances the electron injection and transmission capabilities of the material;

[0069] (2) In the cuprous iodide cluster material modified with phenoxazine provided by the present invention, the steric hindrance effect of the phosphine group effectively suppresses the quenching effect caused by the interaction between molecules;

[0070] (3) The present invention can simultaneously utilize singlet and triplet excitons to emit light, significantly improving the luminous efficiency and brightness of electroluminescent devices;

[0071] (4) The present invention can effectively inhibit the interaction between molecules through the steric hindrance effect of the larger molecules, reduce the quenching effect, and enhance the efficiency and stability of the electroluminescent device;

[0072] (5) The phenoxazine-modified cuprous iodide cluster material provided by the present invention can improve the electron injection and transmission capabilities of the material through the polarization effect of the phosphine oxide group, thereby reducing the driving voltage of the electroluminescent device;

[0073] (6) The synthetic route of the present invention is easy to implement and control, the preparation method is simple, and the target molecular product can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 The UV-visible absorption spectra of compounds 1-4 prepared in the specific embodiments of the present invention are shown;

[0075] Figure 2 The photoluminescence spectra of compounds 1-4 prepared in the specific embodiments of the present invention are shown;

[0076] Figure 3 The relationship curve between brightness and current efficiency of the electroluminescent device prepared by compound 1-4 in the embodiment of the present invention is shown;

[0077] Figure 4 The relationship curve between brightness and power efficiency of the electroluminescent device prepared by compounds 1-4 in the embodiment of the present invention is shown.

[0078] Figure 5 The relationship curve between the brightness and external quantum efficiency of the electroluminescent device prepared by the compound 1-4 in the embodiment of the present invention is shown;

[0079] Figure 6 The voltage-brightness relationship curve of the electroluminescent device prepared by compound 1-4 in the embodiment of the present invention is shown;

[0080] Figure 7 The voltage-current density relationship curve of the electroluminescent device prepared by compound 1-4 in the embodiment of the present invention is shown;

[0081] Figure 8 The electroluminescence spectra of the electroluminescent devices prepared by the compounds 1-4 in the examples of the present invention are shown;

[0082] Fig. 9 The compound 1 in Example 1 of the present invention is shown 1 H NMR spectrum (TMS, CDCl3, 400 MHz);

[0083] Fig.10 The compound 2 in Example 2 of the present invention is shown 1 H NMR spectrum (TMS, CDCl3, 400 MHz);

[0084] Fig.11 The compound 3 in Example 3 of the present invention is shown 1 H NMR spectrum (TMS, CDCl3, 400 MHz);

[0085] Fig.12 The compound 4 in Example 4 of the present invention is shown 1 H NMR spectrum (TMS, CDCl3, 400 MHz). DETAILED DESCRIPTION

[0086] Under anhydrous and oxygen-free conditions, 1mmol of precursor 1 was mixed with 3mmol of tetramethylethylenediamine in an ether solution, and the temperature of the reaction system was lowered to -78°C. After half an hour of temperature control, 3mmol of n-butyl lithium was added dropwise with a constant pressure dropper. After the temperature was controlled for half an hour, the reaction was carried out at room temperature for 16 hours. Then the temperature was controlled at -78°C for half an hour. 3.3mmol of diphenylphosphine chloride was added dropwise with a constant pressure dropper, and the reaction was carried out at room temperature for another 16 hours. 4mmol of hydrogen peroxide was added dropwise with a constant pressure dropper funnel. After oxidation, the product was extracted with water and dichloromethane. The organic layers were combined, dried, and purified by column chromatography using a mixed solvent of dichloromethane and ethyl acetate as the eluent to obtain precursor 2.

[0087] 1mmol of precursor 2 was mixed with 4mL of glacial acetic acid, and 1.2mL of H2SO4 was added dropwise with a constant pressure dropper under an ice-water bath with less ice. After the dropwise addition, the mixture was transferred to an oil bath at 60°C for reaction, and 2mmol of NBS was added in batches. After the reaction was completed, the mixture was quenched with ice cubes. The mixture was then extracted with water and dichloromethane, the organic layers were combined, dried, and purified by column chromatography using a mixed solvent of dichloromethane and ethyl acetate as the eluent to obtain precursor 3.

[0088] Under anhydrous and oxygen-free conditions at 130°C, 1mmol of precursor 3 reacts with 5mmol of phenoxazine, 0.03mmol of palladium acetate and 1.1mmol of potassium tert-butoxide in 10mL of xylene solution, and then 0.09mmol of tri-tert-butylphosphine is added. After passing water, move into an oil bath for 24h. After the reaction is completed, quench with ice water, extract with a large amount of water and dichloromethane, dry with anhydrous sodium sulfate, and spin dry the organic layer. Purify the wet column by flash column chromatography, and the eluent is ethyl acetate and dichloromethane to obtain precursor 5.

[0089] Under anhydrous and oxygen-free conditions at 100°C, 1 mmol of precursor 5 reacted with 15 mmol of trichlorosilane in 15.7 mL of toluene solution, and then moved into an oil bath for 12 hours after passing water. After the reaction was completed, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried. The wet column was purified by flash column chromatography, and the eluent was petroleum ether and dichloromethane to obtain precursor 7.

[0090] Under anhydrous and oxygen-free conditions at 40°C, 1 mmol of precursor 7 was reacted with 2 mmol of cuprous iodide in 40 mL of dichloromethane solution. After passing water, the mixture was moved into an oil bath for reaction for 24 h. The solid was filtered out with acetonitrile to obtain compound 1.

[0091] Under anhydrous and oxygen-free conditions at 130°C, 1 mmol of precursor 3 reacted with 10 mmol of phenoxazine, 0.06 mmol of palladium acetate and 2.2 mmol of potassium tert-butoxide in 20 mL of xylene solution, and then 0.18 mmol of tri-tert-butylphosphine was added. After passing water, it was moved into an oil bath for reaction for 24 hours. After the reaction was completed, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate, and the organic layer was spin-dried. The wet column was purified by flash column chromatography, and the eluent was ethyl acetate and dichloromethane to obtain precursor 6.

[0092] Under anhydrous and oxygen-free conditions at 100°C, 1 mmol of precursor 6 reacted with 15 mmol of trichlorosilane in 15.7 mL of toluene solution, and then moved into an oil bath for 12 hours after passing water. After the reaction was completed, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried. The wet column was purified by flash column chromatography, and the eluent was petroleum ether and dichloromethane to obtain precursor 8.

[0093] Under anhydrous and oxygen-free conditions at 40°C, 1 mmol of precursor 8 was reacted with 2 mmol of cuprous iodide in 40 mL of dichloromethane solution. After passing water, the mixture was moved into an oil bath for reaction for 24 h. The solid was filtered out with acetonitrile to obtain compound 2.

[0094] Under anhydrous and oxygen-free conditions at 130°C, 1mmol of precursor 9 and 1mmol of phenoxazine were reacted in 2mL of N,N-dimethylformamide solution with 3mmol of potassium carbonate and 3mmol of copper powder, and then moved into an oil bath for 24h. After the reaction, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried. The wet column was purified by flash column chromatography, and the eluent was petroleum ether to obtain precursor 10.

[0095] Under anhydrous and oxygen-free conditions at 110°C, 1 mmol of precursor 10 and 1.2 mmol of borate were reacted in 5 mL of 1,4-dioxane solution with 3 mmol of potassium acetate and 0.03 mmol of ferrocene, and then moved into an oil bath for 6-8 hours. After the reaction, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried and purified by flash column chromatography, with petroleum ether and dichloromethane as the eluent to obtain precursor 11.

[0096] Under anhydrous and oxygen-free conditions at 110°C, 1.5 mmol of precursor 11 and 1 mmol of precursor 3 were reacted with 0.025 mmol of tetrakistriphenylphosphine palladium and 3 mmol of sodium hydroxide in 4.5 mL of toluene solution, and 0.05 mL of water was added with a syringe. After passing water, the mixture was moved into an oil bath for reaction for 2-4 hours. After the reaction was completed, the mixture was quenched with ice water, extracted with a large amount of water and dichloromethane, and dried with anhydrous sodium sulfate. The organic layer was spin-dried and purified by wet column chromatography using ethyl acetate as the eluent to obtain precursor 12.

[0097] Under anhydrous and oxygen-free conditions at 100°C, 1 mmol of precursor 12 reacted with 15 mmol of trichlorosilane in 15.7 mL of toluene solution, and then moved into an oil bath for 12 hours after passing water. After the reaction was completed, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried. The wet column was purified by flash column chromatography, and the eluent was petroleum ether and dichloromethane to obtain precursor 14, respectively.

[0098] Under anhydrous and oxygen-free conditions at 40°C, 1 mmol of precursor 14 was reacted with 2 mmol of cuprous iodide in 40 mL of dichloromethane solution. After passing water, the mixture was moved into an oil bath for reaction for 24 h. The solid was filtered out with acetonitrile to obtain compound 3.

[0099] Under anhydrous and oxygen-free conditions at 110°C, 3 mmol of precursor 11 and 1 mmol of precursor 4 were reacted with 0.05 mmol of tetrakistriphenylphosphine palladium and 5 mmol of sodium hydroxide in 4.5 mL of toluene solution, and 0.1 mL of water was added with a syringe. After passing water, the mixture was moved into an oil bath for reaction for 2-4 hours. After the reaction was completed, the mixture was quenched with ice water, extracted with a large amount of water and dichloromethane, and dried with anhydrous sodium sulfate. The organic layer was spin-dried and purified by wet column chromatography using ethyl acetate as the eluent to obtain precursor 13.

[0100] Under anhydrous and oxygen-free conditions at 100°C, 1 mmol of precursor 13 reacted with 15 mmol of trichlorosilane in 15.7 mL of toluene solution, and then moved into an oil bath for 12 hours after passing water. After the reaction was completed, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried. The wet column was purified by flash column chromatography, and the eluent was petroleum ether and dichloromethane to obtain precursor 15, respectively.

[0101] Under anhydrous and oxygen-free conditions at 40°C, 1 mmol of precursor 15 was reacted with 2 mmol of cuprous iodide in 40 mL of dichloromethane solution. After passing water, the mixture was moved into an oil bath for reaction for 24 h. The solid was filtered out with acetonitrile to obtain compound 4.

[0102] The compound 1-4 prepared above was used as the compound 1-4 of the following Examples 1-4, and the UV-visible absorption spectrum was as follows: Figure 1 As shown in the photoluminescence spectrum Figure 2 shown.

[0103] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0104] Example 1

[0105] The electroluminescent yellow-green light emitting device was prepared using a mixture of the compound 1 prepared above and BCPO (bis-4-(N-carbazolylphenyl)phenylphosphine oxide) (wherein the mass fraction of the compound 1 was 20%) as the guest material of the light emitting layer, and the process was as follows:

[0106] 1. The ITO substrate, which had been cleaned 3 to 5 times with acetone, deionized water and anhydrous ethanol respectively, was spin-coated with poly (3,4-ethylenedioxythiophene: polystyrene sulfonate) (PEDOT:PSS) on a clean bench at a rotation speed of 2000 rpm / min to obtain a 40 nm hole injection layer.

[0107] 2. In a glove box, at a rotation speed of 2000 rpm / min, a light-emitting layer was spin-coated on the hole injection layer. The light-emitting layer was BCPO as the main body and doped with 20% of compound 1 to obtain a 40 nm light-emitting layer.

[0108] 3. When the vacuum degree is 2×10 -4 pa and evaporation rate is 3nms -1 Under the conditions of , TmPyPB material was evaporated on the light-emitting layer to obtain a 50nm transmission layer.

[0109] 4. When the vacuum degree is 2×10 -4 pa and evaporation rate is 0.05nms -1 LiF material was evaporated on the electron transport layer under the conditions of to obtain a 1nm electron injection layer.

[0110] 5. When the vacuum degree is 2×10 -4 pa and evaporation rate is 6nms -1 Under the conditions of , metal Al was evaporated on the electron injection layer to obtain a 100nm cathode conductive layer, which was then packaged to obtain an electro-yellow-green light-emitting device.

[0111] The structure of the electroluminescent device in this embodiment is: ITO|PEDOT:PSS (40 nm)|BCPO:Compound 1 (20 wt%, 40 nm)|TmPyPB (50 nm)|LiF ​​(1 nm)|Al (100 nm).

[0112] like Figure 7As shown, the variation trend of the current density of the electroluminescent device with the change of voltage is tested, and it can be known that compound 1 has semiconductor characteristics and its threshold voltage is 4.0V.

[0113] like Figure 6 As shown in the figure, the brightness of the electroluminescent device is tested as the voltage changes, and the maximum brightness of the device can reach 1627cd·m -2 .

[0114] like Figure 3 As shown in the figure, the current efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a brightness of 4.805 cd·m -2 When the current efficiency reaches the maximum value of 95.90cd·A -1 .

[0115] like Figure 4 As shown in the figure, the power efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a power efficiency of 4.805 cd·m -2 When the power efficiency reaches the maximum value of 75.27lm·W -1 .

[0116] like Figure 5 As shown in the figure, the external quantum efficiency of the electroluminescent device is tested for the change trend of the current density, and the device is obtained at a brightness of 4.805 cd·m -2 When , the maximum external quantum efficiency of 35.48% was obtained.

[0117] The electroluminescence spectrum of the electroluminescent device is shown in FIG. Figure 8 As shown by Figure 4 It can be seen that the electroluminescence peak of the device is at 508nm.

[0118] Example 2

[0119] The mixture of compound 2 and BCPO prepared above (wherein the mass fraction of compound 2 is 20%) is used as the guest material of the light-emitting layer to prepare an electroluminescent yellow-green light-emitting device, and the process is the same as that of Example 1.

[0120] The structure of the electroluminescent device in this embodiment is: ITO|PEDOT:PSS (40 nm)|BCPO:Compound 2 (20 wt%, 40 nm)|TmPyPB (50 nm)|LiF ​​(1 nm)|Al (100 nm).

[0121] like Figure 7 As shown, the variation trend of the current density of the electroluminescent device with the change of voltage is tested, and it can be known that compound 2 has semiconductor characteristics and its threshold voltage is 4.2V.

[0122] like Figure 6As shown in the figure, the brightness of the electroluminescent device is tested as the voltage changes, and the maximum brightness of the device can reach 3357cd·m -2 .

[0123] like Figure 3 As shown in the figure, the current efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a brightness of 57.23 cd·m -2 When the current efficiency reaches the maximum value of 156.48cd·A -1 .

[0124] like Figure 4 As shown in the figure, the power efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a power efficiency of 57.23 cd·m -2 When the power efficiency reaches the maximum value of 94.49lm·W -1 .

[0125] like Figure 5 As shown in the figure, the external quantum efficiency of the electroluminescent device is tested for the change trend of the current density, and the device is obtained at a brightness of 57.23 cd·m -2 When , the maximum external quantum efficiency of 50.07% was obtained.

[0126] The electroluminescence spectrum of the electroluminescent device is shown in FIG. Figure 8 As shown by Figure 4 It can be seen that the electroluminescence peak of the device is at 530nm.

[0127] Example 3

[0128] The mixture of compound 3 and BCPO prepared above (wherein the mass fraction of compound 3 is 20%) is used as the guest material of the light-emitting layer to prepare an electroluminescent yellow-green light-emitting device, and the preparation process is the same as that of Example 1.

[0129] The structure of the electroluminescent device in this embodiment is: ITO|PEDOT:PSS (40 nm)|BCPO:Compound 3 (20 wt%, 40 nm)|TmPyPB (50 nm)|LiF ​​(1 nm)|Al (100 nm).

[0130] like Figure 7 As shown, the variation trend of the current density of the electroluminescent device with the change of voltage is tested, and it can be known that compound 2 has semiconductor characteristics and its threshold voltage is 4.5V.

[0131] like Figure 6 As shown in the figure, the brightness of the electroluminescent device is tested as the voltage changes, and the maximum brightness of the device can reach 163cd·m -2 .

[0132] like Figure 3 As shown in the figure, the current efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a brightness of 5.22 cd·m -2 When the current efficiency reaches the maximum value of 6.28cd·A -1 .

[0133] like Figure 4 As shown in the figure, the power efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a power efficiency of 5.22 cd·m -2 When the power efficiency reaches the maximum value of 4.38lm·W -1 .

[0134] like Figure 5 As shown in the figure, the external quantum efficiency of the electroluminescent device is tested for the change trend of the current density, and the device is obtained at a brightness of 5.22 cd·m -2 When , the maximum external quantum efficiency of 2.70% was obtained.

[0135] The electroluminescence spectrum of the electroluminescent device is shown in FIG. Figure 8 As shown by Figure 8 It can be seen that the electroluminescence peak of the device is at 510nm.

[0136] Example 4

[0137] The mixture of compound 4 and BCPO prepared above (wherein the mass fraction of compound 4 is 20%) is used as the guest material of the light-emitting layer to prepare an electroluminescent yellow-green light-emitting device, and the preparation process is the same as that of Example 1.

[0138] The structure of the electroluminescent device in this embodiment is: ITO|PEDOT:PSS (40 nm)|BCPO:Compound 4 (20 wt%, 40 nm)|TmPyPB (50 nm)|LiF ​​(1 nm)|Al (100 nm).

[0139] like Figure 7 As shown, the variation trend of the current density of the electroluminescent device with the change of voltage is tested, and it can be known that compound 4 has semiconductor characteristics and its threshold voltage is 4.0V.

[0140] like Figure 6 As shown in the figure, the brightness of the electroluminescent device is tested as the voltage changes, and the maximum brightness of the device can reach 325.1 cd·m -2 .

[0141] like Figure 3 As shown in the figure, the current efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a brightness of 2.44 cd·m -2 When the current efficiency reaches the maximum value of 23.41cd·A-1 .

[0142] like Figure 4 As shown in the figure, the power efficiency of the electroluminescent device is tested as the brightness changes, and the device is found to have a power efficiency of 2.44 cd·m -2 When the power efficiency reaches the maximum value of 18.37lm·W -1 .

[0143] like Figure 5 As shown in the figure, the external quantum efficiency of the electroluminescent device is tested for the change trend of the current density, and the device is obtained at a brightness of 2.44 cd·m -2 When , the maximum external quantum efficiency is 9.13%.

[0144] The electroluminescence spectrum of the electroluminescent device is shown in FIG. Figure 8 As shown by Figure 8 It can be seen that the electroluminescence peak of the device is at 500nm.

[0145] Examples 1-4 respectively prepared compounds 1-4 1 H NMR spectrum Figure 9-12 As shown, from Figure 9-12 It can be seen that the present invention synthesized compounds 1-4.

[0146] The above are only preferred specific implementations of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A cuprous iodide cluster material modified with phenoxazine, characterized in that: It has one of the following structures:

2. The method for preparing a phenoxazine-modified cuprous iodide cluster material according to claim 1, characterized in that: The steps include: (1) Under anhydrous and oxygen-free conditions, precursor 1 reacts with tetramethylethylenediamine in an ether solution with n-butyl lithium, diphenylphosphine chloride and hydrogen peroxide to obtain precursor 2; (2) Precursor 2 reacts with N-bromosuccinimide in acetic acid and sulfuric acid to obtain precursors 3 and 4; (3) Under anhydrous and oxygen-free conditions, precursors 3 and 4 react with phenoxazine in a xylene solution with palladium acetate, potassium tert-butoxide and tri-tert-butylphosphine to obtain precursors 5 and 6, respectively; (4) Under anhydrous and oxygen-free conditions, precursor 5 and precursor 6 react with trichlorosilane in a toluene solution to obtain precursor 7 and precursor 8, respectively; (5) Under anhydrous and oxygen-free conditions, precursor 7 and precursor 8 react with cuprous iodide in a dichloromethane solution to obtain compound 1 and compound 2, respectively; (6) Under anhydrous and oxygen-free conditions, precursor 9 reacts with phenoxazine in N,N-dimethylformamide solution with potassium carbonate and copper powder to obtain precursor 10; (7) Under anhydrous and oxygen-free conditions, the precursor 10 reacts with the borate ester in a 1,4-dioxane solution by adding potassium acetate and ferrocene to obtain the precursor 11; (8) Under anhydrous and oxygen-free conditions, precursor 11 reacts with precursor 3 and precursor 4 in a toluene solution with tetrakistriphenylphosphine palladium and sodium hydroxide to obtain precursor 12 and precursor 13, respectively; (9) Under anhydrous and oxygen-free conditions, precursor 12 and precursor 13 are reacted with trichlorosilane in a toluene solution to obtain precursor 14 and precursor 15, respectively; (10) Under anhydrous and oxygen-free conditions, precursor 14 and precursor 15 were reacted with cuprous iodide in a dichloromethane solution to obtain compound 3 and compound 4, respectively.

3. The method for preparing the phenoxazine-modified cuprous iodide cluster material according to claim 2, characterized in that: The specific steps include: (1) Under anhydrous and oxygen-free conditions, the precursor 1 is mixed with an ether solution of tetramethylethylenediamine, the reaction system is cooled, and the temperature is controlled for half an hour; n-butyl lithium is added dropwise with a constant pressure dropper, and the temperature is controlled for half an hour after the addition is completed, and the reaction is carried out at room temperature; the temperature is then controlled for half an hour; diphenylphosphine chloride is added dropwise with a constant pressure dropper, and the reaction is carried out at room temperature; hydrogen peroxide is added dropwise with a constant pressure dropper, and after oxidation, it is extracted with water and dichloromethane, the organic layers are combined, dried, and purified by column chromatography using a mixed solvent of dichloromethane and ethyl acetate as an eluent to obtain a precursor 2; (2) Precursor 2 was mixed with glacial acetic acid, and H2SO4 was added dropwise using a constant pressure dropper under an ice-water bath with less ice. After the dropwise addition was completed, the mixture was transferred to an oil bath for reaction, and NBS was added in batches. After the reaction was completed, the mixture was quenched with ice cubes, and then extracted with water and dichloromethane. The organic layers were combined, dried, and purified by column chromatography using a mixed solvent of dichloromethane and ethyl acetate as the eluent to obtain precursors 3 and 4. (3) Under anhydrous and oxygen-free conditions, precursor 3 and precursor 4 are reacted with phenoxazine, palladium acetate and potassium tert-butoxide in a xylene solution, and then tri-tert-butylphosphine is added. After passing water, the mixture is moved into an oil bath for reaction. After the reaction is completed, the mixture is quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried over anhydrous sodium sulfate. The organic layer is spin-dried and purified by wet column chromatography using ethyl acetate and dichloromethane as eluents to obtain precursor 5 and precursor 6, respectively. (4) Under anhydrous and oxygen-free conditions, precursor 5 and precursor 6 were reacted with trichlorosilane in a toluene solution, respectively, and then moved into an oil bath for reaction. After the reaction was completed, the reaction was quenched with ice water, extracted with water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer was spin-dried and purified by wet column chromatography using petroleum ether and dichloromethane as eluents to obtain precursor 7 and precursor 8, respectively. (5) Under anhydrous and oxygen-free conditions, precursor 7 and precursor 8 were reacted with cuprous iodide in a dichloromethane solution, respectively, and then moved into an oil bath for reaction after passing water. The solids were filtered out with acetonitrile to obtain compound 1 and compound 2, respectively; (6) Under anhydrous and oxygen-free conditions, precursor 9 reacts with phenoxazine in N,N-dimethylformamide solution with potassium carbonate and copper powder, and then moves into an oil bath for reaction. After the reaction is completed, it is quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried with anhydrous sodium sulfate. The organic layer is spin-dried and purified by wet column chromatography using petroleum ether as the eluent to obtain precursor 10; (7) Under anhydrous and oxygen-free conditions, the precursor 10 and the borate ester were reacted in a 1,4-dioxane solution with potassium acetate and ferrocene, and then moved into an oil bath for reaction. After the reaction was completed, it was quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried over anhydrous sodium sulfate. The organic layer was spin-dried and purified by flash column chromatography with petroleum ether and dichloromethane as the eluent to obtain the precursor 11; (8) Under anhydrous and oxygen-free conditions, precursor 11 is reacted with precursor 3 and precursor 4 in a toluene solution with tetrakistriphenylphosphine palladium and sodium hydroxide, and water is added with a syringe. After the water is passed, the mixture is moved into an oil bath for reaction. After the reaction is completed, the mixture is quenched with ice water, extracted with water and dichloromethane, and dried with anhydrous sodium sulfate. The organic layer is spin-dried and purified by wet column chromatography using ethyl acetate as the eluent to obtain precursor 12 and precursor 13, respectively. (9) Under anhydrous and oxygen-free conditions, precursor 12 and precursor 13 were reacted with trichlorosilane in a toluene solution, respectively, and then moved into an oil bath for reaction. After the reaction was completed, the precursors were quenched with ice water, extracted with a large amount of water and dichloromethane, and then dried over anhydrous sodium sulfate. The organic layer was spin-dried and purified by wet column chromatography using petroleum ether and dichloromethane as eluents to obtain precursors 14 and 15, respectively. (10) Under anhydrous and oxygen-free conditions, precursor 14 and precursor 15 were reacted with cuprous iodide in a dichloromethane solution, respectively. After passing water, the mixture was moved into an oil bath for reaction. The solids were filtered out with acetonitrile to obtain compounds 3 and 4, respectively.

4. The phenoxazine-modified cuprous iodide cluster material according to claim 1 or the phenoxazine-modified cuprous iodide cluster material prepared according to claim 2 or 3 is used as a luminescent material.

5. The use according to claim 4, characterized in that: The luminescent material is a near-ultraviolet to ultraviolet luminescent thermally excited delayed fluorescent material.

6. Use of the phenoxazine-modified cuprous iodide cluster material according to claim 1 or the phenoxazine-modified cuprous iodide cluster material prepared according to claim 2 or 3 in an electroluminescent device.

7. An electroluminescent device, characterized in that: The phenoxazine-modified cuprous iodide cluster material according to claim 1 or the phenoxazine-modified cuprous iodide cluster material and the host material doped light-emitting layer prepared according to claim 2 or 3 is spin-coated on the hole injection layer.

8. An electroluminescent device according to claim 7, characterized in that: The main material is bis-4-(N-carbazolylphenyl)phenylphosphine oxide.

9. A method for preparing an electroluminescent device according to claim 7 or 8, characterized in that: The steps include:

1. preparing a conductive anode layer; 2. preparing a hole injection layer; 3. preparing a light-emitting layer; 4. preparing an electron transport layer; 5. preparing an electron injection layer; 6. Prepare a cathode conductive layer, encapsulate, and obtain an electroluminescent device of phenoxazine-modified cuprous iodide clusters.

10. The method for preparing an electroluminescent device according to claim 9, characterized in that: The specific steps include:

1. Preparation of Conductive Anode Layer preparing the conductive anode layer on the substrate layer; 2. Preparation of hole injection layer Spin coating a hole injection layer on the conductive anode layer, wherein the hole injection layer material is poly (3,4-ethylenedioxythiophene:polystyrene sulfonate) (PEDOT:PSS); 3. Preparation of the Light Emitting Layer Spin coating the light-emitting layer on the hole injection layer, wherein the light-emitting layer is bis-4-(N-carbazolyl)phenyl)phenylphosphine oxide as a main material and doped with 20% of a phenoxazine-modified cuprous iodide cluster material to obtain the light-emitting layer; 4. preparing an electron transport layer; Vapor depositing TmPyPB material on the light-emitting layer to obtain the electron transport layer; 5. preparing an electron injection layer; Vapor depositing LiF material on the electron transport layer to obtain the electron injection layer; 6. Preparation of cathode conductive layer, Metal Al is evaporated on the electron injection layer to obtain the cathode conductive layer, and then packaging is performed to obtain the electroluminescent device.

Citation Information

Patent Citations

  • Dibenzofuranyl aromatic phosporic-oxygenic compound and preparation method and application thereof

    CN102432637A

  • Multifunctional modified dibenzofuran-based phosphineoxy compound and preparation method and application thereof

    CN102898472A

  • Functional copper diphosphine cluster compound electroluminescent material based on dibenzofuran group, and preparation method and application thereof

    CN106831829A

  • Thermal activation delay materials and organic electro-optical device comprising thermal activation delay materials

    CN109134520A

  • Polynuclear copper complex luminescent material based on phosphine coordination

    CN115716842A